PENGARUH ONLINE CUSTOMER REVIEW DAN PRICE DISCOUNT TERHADAP KEPUTUSAN PEMBELIAN E-COMMERCE SHOPEE PADA MAHASISWA UNIVERSITAS RIAU - Fahrul, Ahmad; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Shopee as the e-commerce with the highest number of visits in Indonesia certainly has advantages that become an attraction. Online customer reviews and price discounts have a role in the process of making product purchase decisions by consumers, especially among University of Riau students. Online customer reviews help students to find out more information about the products they will buy, while price discounts encourage students to make purchases after seeing reviews which are the initial stage before making a purchase decision. Based on this, the purpose of this study is to determine and analyze the influence of online customer reviews and price discounts on Shopee e-commerce purchase decisions in the University of Riau students both partially and simultaneously. The research method used is descriptive research with quantitative methods. The population in this study is students of Riau University. The sampling technique used is probability sampling and the sample is taken by purposive sampling. The measurement scale used is the Likert Scale and data collection using questionnaires. Meanwhile, the analysis technique used is the descriptive statistical method. The results showed that online customer reviews and price discounts influence the purchasing decisions of University of Riau students in shopping at Shopee e-commerce. Simultaneously, online customer reviews and price discounts have an influence and are significant on the purchasing decisions of Universitas Riau students in shopping at Shopee e-commerce. Keyword : online customer review, price discount, purchase decisions